Life Expectancy, Schooling, and Lifetime Labor Supply: Theory and Evidence Revisited. Issue 5 (18th September 2013) - Cervellati, Matteo; Sunde, Uwe
<x xml:space="preserve">Abstract</x> This paper presents a theoretical and empirical analysis of the role of life expectancy for optimal schooling and lifetime labor supply. The results of a simple prototype Ben‐Porath model with age‐specific survival rates show that an increase in lifetime labor supply is not a necessary, or a sufficient, condition for greater life expectancy to increase optimal schooling. The observed increase in survival rates during working ages that follows from the "rectangularization" of the survival function is crucial for schooling and labor supply. The empirical results suggest that the relative benefits of schooling have been increasing across cohorts of U.S. men born between 1840 and 1930. A simple quantitative analysis shows that a realistic shift in the survival function can lead to an increase in schooling and a reduction in lifetime labor hours.